Changes in patient reported outcome measures after treatment for female urethral stricture. Issue 4 (14th March 2021) - Lane, Giulia I.; Gracely, Alyssa; Uberoi, Pansy; Lee, Una; Smith, Ariana L.; Anger, Jennifer T.; Theva, Didi; DeLong, Jessica; Kowalik, Casey; Padmanabhan, Priya; Powell, Charles R.; Carmel, Maude E.; et al.
Abstract: Introduction: There is a paucity of patient reported outcome measure (PROM) data for women with urethral strictures. To address this gap, we aim to evaluate change in PROM among women who underwent surgery for a stricture. Methods: American Urological Association Symptom Index (AUA‐SI) and Urogenital Distress Inventory (UDI‐6) data from a multi‐institutional retrospective cohort study of women treated for urethral stricture was assessed. Results: Fifty‐seven women had either AUA‐SS or UDI‐6 and 26 had baseline and postoperative data for either. Most women underwent urethroplasty (77%) and the majority (73%) remained stricture free at median follow‐up of 21 months (interquartile range [IQR] 7–37). The median baseline AUA‐SI was 21 (IQR 12–28) and follow‐up was 10 (IQR 5–24). After treatment, there was a median decrease of 12 (IQR −18 to −2) in AUA‐SI ( p  = 0.003). The median AUA Quality of life (QOL) score at baseline and follow‐up were 6 (IQR 4–6) and 3 (IQR 2–5), respectively. There was a median AUA‐QOL improvement of 2 points (−5, 0; p  = 0.007) from a baseline 5 (unhappy) to 3 (mixed). Median UDI‐6 scores were 50 (IQR 33–75) at baseline and 17 (IQR 0–39), at follow‐up. After treatment, there was a median decrease of 19 (−31 to −11; p  = 0.01). Conclusion: Women with urethral strictures have severe lower urinary tract symptoms which improved after surgery. This study substantiates the claims that recognizing and treating women with urethral stricture disease greatly improves lower urinary tract symptoms and QOL.